Unplanned Extubation in Patients with Mechanical Ventilation: Experience in the Medical Intensive Care Unit of a Single Tertiary Hospital - Lee, Tae Won; Hong, Jeong Woo; Yoo, Jung-Wan; Ju, Sunmi; Lee, Seung Hun; Lee, Seung Jun; Cho, Yu Ji; Jeong, Yi Yeong; Lee, Jong Deog; Kim, Ho Cheol (Tuberculosis and respiratory diseases, 2015)
Potentially harmful unplanned extubation (UE) may occur in patients on mechanical ventilation (MV) in an intensive care unit (ICU) setting. This study aimed to evaluate the clinical characteristics of UE and its impact on clinical outcomes in patients with MV in a medical ICU (MICU). We retrospectively evaluated MICU data prospectively collected between December 2011 and May 2014. A total of 468 patients were admitted to the MICU, of whom 450 were on MV. Of the patients on MV, 30 (6.7%) experienced UE; 13 (43.3%) required reintubation after UE, whereas 17 (56.7%) did not require reintubation. Patients who required reintubation had a significantly longer MV duration and ICU stay than did those not requiring reintubation (19.4±15.1 days vs. 5.9±5.9 days days and 18.1±14.2 days vs. 7.1±6.5 days, respectively; p<0.05). In addition, mortality rate was significantly higher among patients requiring reintubation than among those not requiring reintubation (54.5% vs. 5.9%; p=0.007). These two groups of patients exhibited no significant differences, within 2 hours after UE, in the fraction of inspired oxygen, blood pressure, heart rate, respiratory rate, and pH. Although reintubation may not always be required in patients with UE, it is associated with a poor outcome after UE.